Tematski premiki v prevodu - Grošelj, Robert (Jezik in slovstvo, 2025)
The paper analyses thematic translation shifts, their obligatoriness and other translation changes that accompany them based on selected Slovene translations of Leonardo da Vinci’s Fables and Legends. The analysis shows that in the translated texts the number of thematic shifts is lower than the number of preserved thematic relations. The thematic shifts are typologically diverse and related to other translation changes, such as vari-ous transformations, rearrangements, omissions or additions of new textual elements. Because of these shifts, typologically, structurally and/or seman-tically different elements appear as target themes, partly changing the the-matic structuring of the text. Most thematic shifts can be considered a result of the translator’s subjective choices, although some were dictated by the systemic differences between Italian and Slovene.
Keywords: Italian; italijanščina; prevodna analiza; sistemska funkcijska slovnica; Slovene; slovenščina; systemic functional grammar; tematski premik; thematic shift; translation analysis